PELATIHAN PEMBUATAN PROFIL KEWIRAUSAHAAN SISWA SMA 2 VII KOTO SUNGAI SARIAK - Elva Dona; Habibatul Hidayati; Henryanto Abaharis; Juarsa Badri; Alfian Alfian; Zusmawati Zusmawati (LPPM Universitas Bina Bangsa, 2022)
The purpose of the training carried out by the community service implementation team is to help students of SMA 2 VII Koto Sungai Sariak use the application in creating their entrepreneurial profile. The training material is the use of the KineMaster application in creating student business profiles. The training is carried out directly at the school. The method of implementing the training is presentation and hands-on practice. The training material was delivered by presenting the use of the KineMaster application directly from the cellphone to the infocus screen using a connector that had been prepared by the service team. The result of this training is that Ninety percent of students (21 people) can use the application on their respective cellphones and another ten percent (2 people) cannot do so with the problem that their existing cellphones do not support downloading applications. In general, students can make video texts that are equipped with audio and can be applied to their business profiles. Difficulties faced by students can be solved directly by the team